The Life and Activities of Slum Youngsters in Praha, Their Hatred of Communist Control and Yearning for the Good Things of the Free West Prompt Them to Rowdyism and High Living - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Item based on interviews conducted with defectors and immigrants in Western refugee camps and immigration offices, or Western travelers returning from stays in East European communist countries, supplemented with information collected through Radio Free Europe (RFE) correspondence with anonymous sources from behind the Iron Curtain. This item was transmitted from the Frankfurt field office. This field report was assigned the following topical and geographical subject headings by the RFE/RL: Czechoslovakia; Youth -- Morale